Advances in European agroforestry: results from the AGFORWARD project - Burgess, Paul J.; Rosati, Adolfo (Springer, 2018)
In global terms, European farms produce high yields of safe and high quality food but this depends on the use of many off-farm inputs and the associated greenhouse gas emissions, loss of soil nutrients and other negative environmental impacts incur substantial societal costs. Farmers in the European Union receive support through a Common Agricultural Policy (CAP) that comprises direct payments to farmers (Pillar I) and payments related to rural development measures (Pillar II). This paper examines the ways in which agroforestry can support European agriculture and rural development drawing on the conclusions of 23 papers presented in this Special Issue of Agroforestry Systems which have been produced during a 4-year research project called AGFORWARD. The project had the goal of promoting agroforestry in Europe and focused on four types of agroforestry: (1) existing systems of high nature and cultural value, and agroforestry for (2) high value tree, (3) arable, and (4) livestock systems. The project has advanced our understanding of the extent of agroforestry in Europe and of farmers’ perceptions of agroforestry, including the reasons for adoption or non-adoption. A participatory approach was used with over 40 stakeholder groups across Europe to test selected agroforestry innovations through field trials and experiments. Innovations included improved grazing management in agroforestry systems of high nature and cultural value and the introduction of nitrogen fixing plants in high value timber plantations and olive groves. Other innovations included shelter benefits for arable crops, and disease-control, nutrient-retention, and food diversification benefits from integrating trees in livestock enterprises. Biophysical and economic models have also been developed to predict the effect of different agroforestry designs on crop and tree production, and on carbon sequestration, nutrient loss and ecosystems services in general. These models help us to quantify the potential environmental benefits of agroforestry, relative to agriculture without trees. In view of the substantial area of European agroforestry and its wider societal and environmental benefits, the final policy papers in this Special Issue argue that agroforestry should play a more significant role in future versions of the CAP than it does at present.
Keywords: Europe; Research Innovation; Land use; Agriculture; Forestry